HKUST-1 MOF: a matrix to synthesize CuO and CuO-CeO2 nanoparticle catalysts for CO oxidation - Zamaro, Juan Manuel (2012)
The oxidation of carbon monoxide using the metal organic framework (MOF) HKUST-1 is studied. Catalytic results and characterizations by XRD, TEM, H2-TPR, SEM and LRS show that HKUST-1 itself is not effective in CO oxidation, but is activated in the reaction atmosphere segregating active 5–15 nm CuO particles upon the collapse of the MOF structure. Furthermore, the microporous structure of HKUST-1 is effective to disperse Ce precursors which, upon activation, allow the synthesis of a mixture of CuO and CeO2 nanoparticles in intimate contact. These nanoparticles present a very high activity in CO oxidation. It is shown that this synthesis route employing HKUST-1 as a matrix is useful to immobilize CuO–Ce2O nanoparticles in a monolithic reactor, while keeping a high catalytic activity.